Perception of the role of physical and rehabilitation medicine among physiotherapy students - Piotr Tederko; Marek Krasuski; Marek Łyp; Anna Cabak; Dariusz Białoszewski; Iwona Stanisławska; Beata Tarnacka (Medical Journals Sweden, 2018)
Objective: To determine how the role of physical and rehabilitation medicine specialists in healthcare is perceived by physiotherapy students. Design: Cross-sectional observational study. Subjects: A total of 677 physiotherapy students and 519 final year medical students at the largest university-level educational institutions in Warsaw, Poland. Methods: Questionnaire about knowledge of the role of physical and rehabilitation medicine specialists in the healthcare system. Results: The definition of physical and rehabilitation medicine specialists was known to 32.9% of medical students and 19.9% of physiotherapy students. Misconceptions most frequently resulted from an inability to distinguish physical and rehabilitation medicine from physiotherapy. The leading role of physical and rehabilitation medicine specialists in team management of persons with disabilities was identified by 25.4-55.5% of medical and 5.8-9.0% of physiotherapy students. Discussion: Inadequate perception of the role of physical and rehabilitation medicine specialists in healthcare may result from recent changes in the management of rehabilitation services, tendencies towards professional independence among health professionals, and insufficient formative education. Conclusion: Perception of the role of physical and rehabilitation medicine specialists in healthcare was found to be inadequate among physiotherapy students. Changes in health professional education are warranted to maintain an effective patient-centred collaborative practice. Further research is needed at national and international levels to address the mutual perception of competencies and roles among students of health professions.